214k views
2 votes
How to solve : (s+t)^3


User Kaminari
by
4.4k points

2 Answers

6 votes

Explanation:

Hey there!

Here, given;


( {s + t)}^(3)

Use formula:


( {a + b)}^(3) = {a}^(3) + 3 {a}^(2)b + 3a {b}^(2) + {b}^(3)

Keep this formula in the question.


( {s + t)}^( 3) = {s}^(3) + 3 {s}^(2) t + 3s {t}^(2) + {t}^(3)

Hope it helps...

User Sergio Mazzoleni
by
5.3k points
3 votes

Answer:


s^3+3s^2t+3st^2+t^3

Explanation:


(s+t)^3\\\\\mathrm{Apply\:Perfect\:Cube\:Formula}:\\\quad \left(a+b\right)^3=a^3+3a^2b+3ab^2+b^3\\\\a=s,\:\:b=t\\=s^3+3s^2t+3st^2+t^3

User Mburakkalkan
by
5.2k points